2023
DOI: 10.1186/s12882-023-03150-0
|View full text |Cite
|
Sign up to set email alerts
|

Validated risk prediction models for outcomes of acute kidney injury: a systematic review

Abstract: Background Acute Kidney Injury (AKI) is frequently seen in hospitalized and critically ill patients. Studies have shown that AKI is a risk factor for the development of acute kidney disease (AKD), chronic kidney disease (CKD), and mortality. Methods A systematic review is performed on validated risk prediction models for developing poor renal outcomes after AKI scenarios. Medline, EMBASE, Cochrane, and Web of Science were searched for articles that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…Серед потенційних переваг цих біомаркерів -очевидна специфічність для ішемічного ураження нирок. Автори наголосили, що рівні KIM-1 і NAG у сечі значно підвищувались при гострому ураженні нирок [14].…”
Section: оригінальні дослідженняunclassified
“…Серед потенційних переваг цих біомаркерів -очевидна специфічність для ішемічного ураження нирок. Автори наголосили, що рівні KIM-1 і NAG у сечі значно підвищувались при гострому ураженні нирок [14].…”
Section: оригінальні дослідженняunclassified
“…The duration of renal function recovery is increasingly recognized as a pivotal factor in predicting patient outcomes [ 4 ]. Studies have shown a correlation between prolonged AKI and heightened risks of complications and mortality [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%